A248 EARLY INITIATION OF STOMACH NEOPLASIA THROUGH DUAL DELETION OF MESENCHYMAL BMP SIGNALING AND TRP53. (1st March 2018) - Ouellet, C; Garde-Granger, P; Boudreau, F; Perreault, N
Abstract: Background: Bone morphogenetic proteins (BMP) are crucial for bidirectional signaling between mesenchyme and epithelium of the gastrointestinal track. Disruption of its signaling is linked to gastric cancer. Our team previously showed that epithelial loss of BMP signaling does not lead to neoplasia while its deletion in the mesenchyme ( Bmpr1a Δ MES ) promotes benign polyposis starting at 90 days without progression. p53 mutation is observed in half of advanced gastric cancer. Interestingly, Bmpr1a Δ MES mice present gastric epithelial p53 accumulation suggesting that it might act to restrain cancer progression. Aims: To investigate if a reactive mesenchyme combined with a primed oncogenic gastric epithelium can promote early gastric neoplasia and progression. Methods: A compound mutant mouse model with a mesenchymal deletion of Bmpr1a and an ubiquitous deletion of Trp53 ( Bmpr1a Δ MES : Trp53 null, double KO) was generated. Macroscopic and histological analyses as well as immunostaining against neoplasia markers were performed on stomach sections of 30 day-old mice from control and experimental groups. Results: At the macroscopic level, 30 day-old double KO mice showed polyps in contrast to controls. Histological analysis revealed early gastric neoplastic initiation, stromal hyperplasia and loss of glandular architecture in double KO mice. PCNA immunostaining revealed mesenchymal and epithelial hyperproliferation in these mice while Bmpr1a ΔMES mice only presented mesenchymal hyperproliferation. Two gastric pre-neoplastic lesions criteria were used to identify neoplasia initiation. The gastric mucosa from double KO 30 day-old mice showed SPEM (transdifferentiation of chief cells and mucous neck cells) in addition to intestinal metaplasia in contrast to 30 day-old Bmpr1a Δ MES mice. An increase in total CD44 positive cells, a cancer stem cell marker, was observed in epithelial and mesenchymal compartments for both Bmpr1a Δ MES and double KO mice. CD44v6 staining, which is usually specifically increased in gastric cancer, was stronger in double KO mice as compared to Bmpr1a Δ MES mice. No histological or molecular changes were observed in the controls. Finally, benin adenomas were observed in Bmpr1a ΔMES mice at 90 days while double KO mice showed cancer progression by exhibiting tubular intramucosal invasive carcinomas around the same age. Conclusions: Our results suggest that a synergic collaboration must exist between the mesenchymal BMP signaling and epithelial p53 to prevent early gastric neoplasia and further progression into carcinomas. Transcriptomic analysis coupled to organoid cultures are ongoing to better dissect the molecular mechanisms involved in these pro-oncogenic signaling events. Funding Agencies: CIHRFRQS